Assessment of weld line performance of PP/Talc moldings produced in hot runner injection molds - Morelli, Carolina L. (2007)
Weld lines are weak regions in thermoplastic injection moldings caused by low molecular entanglement and unfavorable orientation. Their occurrence may lead to a significantly reduced mechanical performance of the products. Therefore, when weld lines are likely to occur in molded products, they must be taken into account during the mechanical and technological design processes. The weld lines become more critical when particulate fillers are compounded with the polymer. The performance of weld lines in talc-filled polypropylene box moldings produced with a double-gated hot runner mold is assessed in this work. The processing conditions were varied in order to cause morphology and tensile-impact resistance changes. The weld performance at room temperature was assessed in terms of the energy absorbed in the impact tests. It was found that the performance depends on the injection temperature, the injection rate, and the orientation of the talc particles in the weld-line plane.